Retail Brand Equity and Loyalty Analysis in the Context of Sector-Specific Antecedents, Perceived Value, and Multichannel Retailing - Weindel, Julia Katharina (Handel und Internationales Marketing Retailing and International Marketing, 2016)
Julia Weindel provides novel implications for researchers and managers by first identifying the sector-specific main levers of retail brand equity. Second, she shows that retail brand equity and perceived value have a reciprocal relationship. The author analyzes which one of these has stronger effects on loyalty. Third, she addresses the interdependencies between brand beliefs, retail brand equity, and loyalty within multichannel retail structures. The study is forced through the knowledge that management of retail brands is highly valuable for scholars and managers, because retail brand equity is known to strongly influence consumer behavior in various contexts. The retail brand represents a valuable asset for retailers which need to know the levers of retail brand equity. Contents Sector-Specific Antecedents of Retail Brand Equity Reciprocity Between Perceived Value and Retail Brand Equity Interdependencies Within Multichannel Retail Structures Target Groups Researchers and students focusing on retailing and marketing Executives and managers interested in the management of retail brands in brick-and-mortar and multichannel retail environments About the Author Dr. Julia Katharina Weindel received her doctoral degree from the University of Trier, where she worked at the Chair for Marketing and Retailing.